1987
DOI: 10.1021/jf00078a018
|View full text |Cite
|
Sign up to set email alerts
|

Total phenolics and high-performance liquid chromatography of phenolic acids of avocado

Abstract: Kansas 66045. acid, and one or more phenyl hydroxyl groups that may become methylated to produce methoxy groups. Phenolic acids commonly occur as esters and/or ethers in combination with various sugars and aliphatic or aromatic acids and hydroxy acids. Most plant phenolic acids are derivatives of either benzoic (benzenecarboxylic; Cg-C^o r cinnamic (phenylpropanoid or phenylacrylic; C6-C3) acids (Roston and Kissinger, 1982).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
1
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(60 citation statements)
references
References 14 publications
4
53
1
2
Order By: Relevance
“…A few studies have focused on the phytochemical composition of P. Americana (Torres et al, 1987). P. americana leaves have been reported to possess antiinflammatory (Adeyemi et al, 2002), antifungal (Prusky et al, 1991) and antibacterial activities (Gomez-Flores, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have focused on the phytochemical composition of P. Americana (Torres et al, 1987). P. americana leaves have been reported to possess antiinflammatory (Adeyemi et al, 2002), antifungal (Prusky et al, 1991) and antibacterial activities (Gomez-Flores, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Phenols were determined using Folin-Ciocalteu protocol as described by Torres et al (1987). The analyses were done in triplicates using gallic acid as a standard.…”
Section: Quantification Of Phenolics and Flavonoidsmentioning
confidence: 99%
“…The amount of total phenolics was calculated in mg gallic acid equivalents/g dry seed material. For the determination of flavonoids, 500 µl of phenolic extracts was analysed using a protocol by Torres et al (1987). Total flavonoids were determined as catechin equivalent from the calibration curve of catechin standard solutions and expressed as mg catechin equivalents/g seed material.…”
Section: Quantification Of Phenolics and Flavonoidsmentioning
confidence: 99%
“…The phenolics found were p-hydroxybenzoic, protocatechuic, βresorcyclic, γ-resorcyclic, α-resorcyclic, gallic, isovanillic, vanillic, syringic, o-coumaric, m-coumaric, pcoumaric, caffeic, ferulic, and sinapic acids. (21) Work by Golukcu1 and Feramuz Ozdemir (22) on "Bacon", "Zutano", "Fuerte", and "Hass" indicated that protocatechuic acid, caffeic acid, (-)-epicatechin, and rutin were the main phenolic compounds. Although differences were noted in the phenolic composition of the fruit the general trend was that o-coumaric acid and rutin contents increased from the first to the second harvesting period (between January and February) and decreased from the second to the third harvesting period (between February and March).…”
Section: Fruit Nutritional Composition and Aroma Volatilesmentioning
confidence: 99%